A Investigação Histórica na Formação de Professores de Matemática - Mendes, Iran Abreu (Revista Cocar, 2011)
Neste artigo discuto a importância da investigação em história da Matemática na formação de professores de Matemática, a partir de ações didáticas realizadas na formação continuada de professores da Educação Básica. Após identificar algumas dificuldades conceituais acerca da Matemática ensinada pelos professores, tomei a história da Matemática como organizador didático e conceitual da Matemática escolar, tomei a investigação histórica da Matemática como um modelo de ensino de Matemática para os professores da Educação Básica. Ao final do estudo, percebi que os textos e as atividades elaboradas contribuíram para a melhoria da prática desses professores nas ações didáticas de sala de aula. Palavras-chave: História da Matemática. Investigação Histórica. Formação de Professores. The historical inquiry in the formation of mathematics teachers In this article I discuss the importance of the inquiry into the history of Mathematics to the formation of Mathematics teachers, starting from didactic actions carried out on the continued education of teachers of Basic Education. Following the identification of a few conceptual difficulties concerning the Mathematics taught by the teachers, I considered the history of Mathematics as a didactic and conceptual organizer of school Mathematics, and I also considered the historical inquiry of Mathematics as a model of Mathematics teaching for the teachers who work with Basic Education. At the end of the study, I noticed that the texts and the activities that were prepared contributed to the improvement of those teachersâ€™ practice regarding classroom didactic actions. Keywords: History of Mathematics. Historical inquiry. Teacher formation